The Analysis of Public Service Expense Policy in the Regional Budget - Koeswara, Hendri; Liesmana, Roza (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2014)
The research answers the questions: How is the growth of Solok Regional Budget in the budget year of 2009-2012? How is the budget allocated for public services in the budget year of 2009-2012? What consideration is taken by the Regional Government in determining regional budget from the aspect of expense and regional expense management policies? What models are used in the allocation of public service expense in the Regional Budget? The stages of the research are: 1. Conducting comparison on the number of annual public service expenses, 2. Viewing the greatest and smallest allocation of public service expenses, 3. Studying whether the allocated budget is in accordance with the government policy. This stage altogether maps the dynamic of Regional Budget arrangement to see the involvement of each actor in the process of budget formulation. The research uses qualitative research method with the data collection technique of in-depth interview and analysis on the Regional Budget documents. First, the entire data, ethic and emic, were analyzed and described, then reduced by making abstraction, as a core summary. Eventually a conclusion was drawn to give a picture of how to make optimum the allocation of public service expenses in the Regional Budget.